Environmental crisis, sectoral versus integral: The agency of change - Zevenbergen, Chris; Hein, Carola; Marcus, Lars (Journal of Delta Urbanism, 2022)
Today we experience and acknowledge the nexus of ecology, culture and politics as a moving objective, defined by local realities placed within global developments. Large-scale change is no longer a distant probability but an approaching condition, which forces us to accept instability and envision sustainability transitions as the ground of future inhabitation. When looking closer into atmospheric, water (riverine, maritime, deltaic), and land systems and their inherent uncertainties we realize the agency that local sensitivities, culture and planning regimes have in defining the success or failure of sustainable development. This dialogue will question what the real ground of preMarsent and future urbanization is, imagining adaptive and transformative change as material and ecologically sensitive practices to site, context and culture. This dialogue is the transcription of the round table talk on the International Forum on Urbanism held in Delft on 26 November 2021. Lars Marcus, Chris Zevenbergen and Carola Hein presented their work in the light of the environmental crisis, sectoral versus integral: the agency of change. With moderator Fransje Hooimeijer they elaborated and related their work in a discussion around the main questions of history, the longue durée, disciplinarity and agency of change.